Quality production of kharif onion (Allium cepa) in response to biofertilizers inoculated organic manures - YEPTHO, AVITOLI K; SINGH, A K; KANAUJIA, S P; SINGH, V B (The Indian Journal of Agricultural Sciences, 2012)
Onion (Allium cepa L.) is a highly nutrient responsive vegetable crop. In the light of fragmental information available on the response of kharif onion to biofertilizers enriched organic manures, a field experiment was conducted during rainy (kharif) season of 2006–08 on acidic kaolinitic Rhodustalf soil representing foothill conditions of Nagaland. Amongst different organic manures, poultry manure produced the highest response on bulb yield (21.18 tonnes/ha), followed by FYM (16.74 tonnes/ha), vermicompost (14.37 tonnes/ha) = pig manure (12.74 tonnes/ha). Incorporation of Azotobacter chroococcum into different organic manures failed to improvise any significant changes in bulb yield due to high initial microbial abundance in organic manures. Different growth-attributing characters followed the similar response. Poultry manure similarly registered highest nutrient uptake as kg/ha (26.39 N – 10.91 P – 55.96 K), followed by FYM (22.80 N – 9.10 P – 47.90 K) with Pig manure and vermicompost (15.08/16.72 N – 7.30/10.91 P – 51.02/55.96 K) displaying no significant difference. Economic analysis in terms of cost : benefit ratio supported these observations. These studies proposed that if organic manures possess enough initial microbial load, the biofortification of organic manures need not be exercised.